Componential Analysis of Indonesian Immigration Terms And Their Translations In English - Yohana Wandira, Ni Komang (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2016)
Nowadays, translation becomes more essential in people’s everyday communication. This is due to people’s mobility in and out from one country into another. This also happens in Indonesia where people from all over the world come to Indonesia not only for travelling but also for other purposes such as investing, working, studying as well as retiring. Thus, the translations of Law in Indonesian Immigration should be taken into account so that the regulation is easily understood and read by those people. The selected data taken from two translation versions of Undang-UndangNomor 6 Tahun 2011 tentangKeimigrasian were analyzed based on the theory of textual equivalence proposed by Allan (1986), supported by Newmark’s Componential Analysis Theory (1988). The result showed that some translations of the Indonesian Immigration Terms into English in both versions are commonly used in the Immigration section such as sponsor, permanent resident permit, Immigration Clearance etc. Some are not common in daily use such as guarantor, temporary resident permit, etc. The translation equivalents were found using componential analysis. However, in some cases,componential analysis theory is insufficient to describe the words in both versions. Therefore, meaning postulate is also applied
Keywords: legal translation, Immigration terms, componential analysis